Sustainable, Economic, and Simple Preparation of an Efficient Catalyst for Li–O2 Batteries - Aguirre-Quintana, M; Aguirre-Quintana, M (Elsevier B.V., 2022)
Developing efficient electrocatalysts for oxygen reduction reaction (ORR) is fundamental to bring the Li–O2 technology closer to practical applications. However, the majority of studied catalysts for this application are either precious metals or cobalt based, which represents an obstacle for a larger scale development, both from an economical and a political point of view. In this work a simple, fully sustainable, and economic synthesis process is used to in situ nucleate SnO2 nanoparticles on the surface of commercial carbon black (C45) by taking advantage of its numerous nucleation sites to deposit and chemically anchor SnO2 nanoparticles. Such synthesis can easily be carried out through wet impregnation, without any acid treatment or high temperature process. The obtained composite material shows an optimal ORR activity, which is confirmed in Li–O2 cells. Indeed, compared to pure C45 air-cathodes, the composite cathodes lead to the formation of much more reversible film-like discharge products, allowing for reduced overvoltage and therefore improved cycling performances both at the high current density of 0.5 mA cm−2 with more than 70 cycles and in prolonged discharge/charge conditions with over 1250 h of operation at the fixed capacity of 2.5 mAh cm−2. © 2022 Elsevier B.V.